2015
DOI: 10.1001/jamapsychiatry.2014.2482
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine Extended-Release for Depression Following Spinal Cord Injury

Abstract: IMPORTANCE Depression is prevalent and associated with negative outcomes in individuals with spinal cord injury (SCI). Antidepressants are used routinely to treat depression, yet no placebo-controlled trials have been published in this population to our knowledge. OBJECTIVE To determine the efficacy and tolerability of venlafaxine hydrochloride extended-release (XR) for major depressive disorder (MDD) or dysthymic disorder in persons with chronic SCI. DESIGN, SETTING, AND PARTICIPANTS Multisite, randomized (1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 67 publications
1
31
1
Order By: Relevance
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
“…The SDS is a validated measure of functional impairment that has demonstrated sensitivity to impairment and the effects of treatment across a wide range of disorders, including MDD (Sheehan & Sheehan, 2008). The SDS has been used to assess functional improvement in association with improvements in depressive symptoms for duloxetine (Mancini et al., 2012; Oakes et al., 2012; Sheehan et al., 2011; Wise et al., 2008), desvenlafaxine (Dunlop et al., 2011; Guico‐Pabia et al., 2012; Soares et al., 2009), paroxetine (Wise et al., 2008), bupropion (Hewett et al., 2010; Soczynska et al., 2014), escitalopram (Romera et al., 2012; Soczynska et al., 2014), venlafaxine (Fann et al., 2015; Hewett et al., 2010), levomilnacipran (Asnis et al., 2013; Sambunaris, Bose, et al., 2014), and agomelatine (Montgomery, Nielsen, et al., 2014; Zajecka et al., 2010) with results that have been variable with respect to clinical significance; however, many of these antidepressants showed significant differences versus placebo in the change from baseline versus placebo in the SDS total score when patients were stratified by baseline depressive symptom severity. A recent pooled analysis showed that treatment with duloxetine ( n  = 1,029) and SSRIs ( n  = 835) resulted in significantly greater improvements in the SDS total score (∆ −1.9, p  <   .001; ∆ −1.7, p  <   .01, respectively) compared to placebo ( n  = 329).…”
Section: Discussionmentioning
confidence: 99%
“…The methodology and primary results can be found elsewhere. 25,28 The study was approved by each of the respective site's internal review board.…”
Section: Methodsmentioning
confidence: 99%
“…In the parent trial, 25 a total of 2536 subjects with traumatic SCI were screened and 133 were eligible for and consented to the trial. Sixty-four individuals were randomized to receive placebo and 69 individuals were randomized to the venlafaxine condition.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Importantly, the first multisite randomized clinical trial of an antidepressant therapy (Venlafaxine XR) for depression among patients with SCI provides critical insights into the potential benefits and possible limitations of this approach. 17 The success of any intervention for depression post-SCI is contingent upon the information obtained in comprehensive, valid and empirically-supported assessments of the correlates, comorbidities, and modifiable risk factors that appear in the Kraft and Dorstyn study and others that do not (e.g. specific type of pain experienced, self-management skills).…”
Section: Timothy R Elliottmentioning
confidence: 99%